Elaboración de una bebida a partir de la leche de soya (Glycine max) saborizada con pasta de cacao (Theobroma cacao) utilizando varios tipos de edulcorantes - Proaño Chillogalli, Jhoana Elizabeth. (2018)
The objective of this investigation was to elaborate a drink from milk of soybean (Glycine max), flavored with paste cocoa (Theobroma cacao) using several types of sweeteners; presenting and providing consumers both adults and children with new food options and, favoring their health conditions through the nutritional advantages of soy. To evaluate the possibility of innovating a soy drink flavored with organic type cocoa paste that corresponds to the commercialization of soy-based products, for this a trifactorial design was applied, A * B * C, where the Factor A is the concentration of soy milk (50 mL, 36 mL); factor B the concentration of cocoa paste (5 g and 10 g) and the C factor are types of sweeteners (Sucrose, Panela, Stevia) with 12 treatments and 3 repetitions, giving a total of 36 experimental units conformed by an approximate 250mL for Each sample packed for further analysis. Physical chemical analyzes were carried out, such as acidity, soluble solids, pH, turbidity, and the sensory analysis was carried out, evaluating the variables of color, smell, taste and appearance of the product. The best treatment that was obtained and for its best results was a0b0c2 (50 mL of soy milk + 5 g of Cocoa paste + 3 g of Stevia) which provides favorable results in acidity (1.83%), soluble solids (6, 2), density (1.05g / mL), turbidity (16.13NTU), pH (6.97), being the soluble solid variables, pH and turbidity presenting significant difference between the treatments; in those treatments that did not observe significant differences with acidity and density. As for the results of the sensory analysis, excellent acceptance was obtained regarding color, smell, taste and appearance, as well; in the other variables, the results between treatments were not differentiated.